2020
DOI: 10.1177/1528083720934198
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to construct antimicrobial surface by decorating polyacrylonitrile nanofibrous membrane with nanoparticles

Abstract: In this paper, polyacrylonitrile (PAN) nanofibrous membranes (NFMs) were prepared by electrospinning technology. Copper (Cu) or/and zinc (Zn) nanoparticles (NPs) were deposited on the surface of PAN NFMs by spark ablation technology to fabricate a surface structure with antibacterial and hydrophobic properties. The deposition of NPs was controlled using current, voltage, carrier gas flow rate, and load time. The fabricated NFMs were characterized by FE-SEM, EDX, XRD, and water contact angle. Moreover, the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The preparation of copper/copper oxide nanofibrous materials became a prevalent topic thanks to a vast range of applications of such nanomaterials, including catalysis [1,2], disinfection [3], antiviral nanocomposites [4], antibacterial wound dressings [5,6], sensors [7], CO 2 electrocatalytic reduction [8] and others. The advantage of using Cu nanofibers instead of other forms of nano or micromaterials is their high surface-to-volume ratio, the possibility to prepare sheets or foils of Cu nanofibers without any limitations in terms of their size, the opportunity to run the continuous roll-to-roll process, and its scalability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of copper/copper oxide nanofibrous materials became a prevalent topic thanks to a vast range of applications of such nanomaterials, including catalysis [1,2], disinfection [3], antiviral nanocomposites [4], antibacterial wound dressings [5,6], sensors [7], CO 2 electrocatalytic reduction [8] and others. The advantage of using Cu nanofibers instead of other forms of nano or micromaterials is their high surface-to-volume ratio, the possibility to prepare sheets or foils of Cu nanofibers without any limitations in terms of their size, the opportunity to run the continuous roll-to-roll process, and its scalability.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches were employed to prepare Cu-containing nanofibers: electroless deposition on a nanofibrous foil as a template [8], self-assembly method using PANI nanofibers as a template [9], incorporation of Cu by admixture of Cu nanoparticles to the electrospinning solution [10], and decoration of nanofibers with Cu nanoparticles [5].…”
Section: Introductionmentioning
confidence: 99%
“…As such, there are a limited number of free hydrophilic nitrile groups that can interact with water molecules and cause the observed wetting behavior of the neat PAN fibers (Figure b). Interestingly, a similar wettability behavior has been reported for the electrospun PAN nanofibers decorated with Cu, Zn, or Cu/Zn nanoparticles (WCA ≈ 129°–136°) as compared to the neat electrospun PAN nanofibers (WCA ≈ 46°) . The surface of the neat PAN fibers is smooth (Figure a).…”
Section: Results and Discussionmentioning
confidence: 95%
“…Interestingly, a similar wettability behavior has been reported for the electrospun PAN nanofibers decorated with Cu, Zn, or Cu/Zn nanoparticles (WCA ≈ 129°−136°) as compared to the neat electrospun PAN nanofibers (WCA ≈ 46°). 29 The surface of the neat PAN fibers is smooth (Figure 3a). However, when the iron hydroxide nanoparticles were deposited on the PAN fabric, the observed morphology of the individual fibers was changed due to the presence of micro/nanostructured features on the surface of the modified fibers (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…8–11 Previous studies showed that copper exhibited broad-spectrum biocide effects and cost-effectiveness, which expanded the application in the fields of clothing, decoration, and medical care. 10–15 Other studies indicated that copper nanoparticles possessed notably increased physicochemical and antibacterial properties in comparison with copper micro particles, which was attributed to their higher surface-to-volume ratio. 12–14 Jiao et al.…”
mentioning
confidence: 99%